2017
DOI: 10.1002/cmdc.201700044
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pieces for the Emerging Picture of Sulfoximines in Drug Discovery: Synthesis and Evaluation of Sulfoximine Analogues of Marketed Drugs and Advanced Clinical Candidates

Abstract: Sulfoximines have gained considerable recognition as an important structural motif in drug discovery of late. In particular, the clinical kinase inhibitors for the treatment of cancer, roniciclib (pan‐CDK inhibitor), BAY 1143572 (P‐TEFb inhibitor), and AZD 6738 (ATR inhibitor), have recently drawn considerable attention. Whilst the interest in this underrepresented functional group in drug discovery is clearly on the rise, there remains an incomplete understanding of the medicinal‐chemistry‐relevant properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(90 citation statements)
references
References 103 publications
1
89
0
Order By: Relevance
“…Organosulfur(VI) derivatives with S=N bonds (e.g., sulfoximines or sulfonimidamides) have attracted much interest recently . It was shown that these compounds can be considered as bioisosteres of sulfones and sulfonamides, respectively (Figure ), with improved physicochemical characteristics and pharmacokinetic profile . It is not surprising, therefore, that significant synthetic efforts have been put into the development of convenient methods for their preparation …”
Section: Introductionmentioning
confidence: 99%
“…Organosulfur(VI) derivatives with S=N bonds (e.g., sulfoximines or sulfonimidamides) have attracted much interest recently . It was shown that these compounds can be considered as bioisosteres of sulfones and sulfonamides, respectively (Figure ), with improved physicochemical characteristics and pharmacokinetic profile . It is not surprising, therefore, that significant synthetic efforts have been put into the development of convenient methods for their preparation …”
Section: Introductionmentioning
confidence: 99%
“…In contrast to sulfones 1 , sulfoximines 2 offer an additional point for substitution, namely the mildly basic nitrogen atom, which can also be utilized for the construction of cyclic sulfoximines 3 (Figure ), for example by connecting the substituents R 2 and R 3 . Recent reports have suggested that the introduction of NH‐sulfoximines 2 (R 3 =H) into certain lead structures can result in reduced Caco2 permeability and increased efflux . In principle, masking of the hydrogen‐bond donor function of the sulfoximine NH group ( 2 , R 3 =H) by N‐alkylation ( 2 , R 3 =alkyl) should be a means to improve membrane permeability, but there are only scattered reports.…”
Section: Introductionmentioning
confidence: 99%
“…[7] However, sulfoximine (an isostere of sulfone)-containing compounds are less explored for their therapeutic use, despite being discovered over six decades ago. It is only in the last 10 years that the synthesis of bioactive sulfoximine derivatives started to pick up momentum due to their favorable physicochemical properties, [19][20][21] hydrogen-bond acceptor/ donor functionalities, [20,21c] relatively higher metabolic stability, [21a,21b] and solubility [21] than the corresponding analogues. The presence of a stereogenic center at the sulfur atom and amenability for further derivatization are additional attractive features of sulfoximines in medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%